Performance analysis on detection and prevention of wormhole attack in wireless network - Apandi, Mohamad Aiman Hanif (2019)
In the wireless network, there is an attack called Wormhole attack that capable in confusing the route of packets during packet transmission and causing data loss. Ad hoc On-Demand Distance Vector (AODV) is routing protocol is usually where the Wormhole attacks happen. This routing protocol is designed for Mobile Ad hoc Network (MANET) and wireless. Ad hoc is a decentralised wireless network which not rely to another device such as router. Due to the use of AODV protocol with limited security during packet delivery, wireless network often suffers from Wormhole attack which causes significant performance restrictions such as low throughput, high end-to-end packet delay and low packet delivery ratio. This project explained the performance analysis on detect and prevent of Wormhole attack in MANET by using tunnelling method among neighbour nodes in AODV protocol environment to ensure the packets safely delivered to destination. The system will prevent Wormhole node remain in the network, which surely improves the performance of wireless network. The simulation experiments using Network Simulator 2 (NS2) have been carried out to analyse the performance of the proposed work. The simulation results show that the proposed work outperforms because the increase numbers of throughput about 36 percent and packet delivery ratio increase 90 percent compared to when Wormhole node in the network. In addition, the proposed work also reduces the end-to-end packet delay about 64 percent compared to before proposed work being implemented. As a result, wireless network communication using AODV protocol now more safe and secure due to malicious attack cannot enter into the system.